Results of reconnaissance surveys of arboretum of A.N. Bukeikhan Kazakh research institute of forestry - Mukhtubayeva, S.K.; Kuanyshbaev, N.K.; Zhamangara, A.K.; Sidakov, K.S.; Razhanov, M.R.; Khadiev, R.M. (Fundamental and Experimental Biology, 2023)
The article presents the results of the inventory of trees and shrubs of arboretum of A.N. Bukeikhan Kazakh research institute of forestry. The paper presents the taxonomic composition of 23 quarters with the identification of dominant plant forms and an assessment of the sanitary condition of plants by category. The taxonomic composition of tree and shrub plantations is represented by 42 genera, 22 families of 14 orders from the departments – Gymnospermae, Angiospermae. Of the identified 22,489 trees and shrubs, 89.6% are deciduous and 10.4% coniferous. The greatest taxonomic diversity was noted in the families Rosaceae and Pinaceae. It has been established that most plants belong to the first category. Quarters 18, 19.2, 22, 23 turned out to have the largest number of plants belonging to 5, 6 categories, which are recommended for removal. The arboretum has a large resource of trees and shrubs, acclimatized and adapted to the climatic features of Northern Kazakhstan, and can serve as a key object for the concentration of genetic diversity.